2021
DOI: 10.21203/rs.3.rs-257573/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic optimization of COVID-19 vaccine prioritization in the context of limited supply

Abstract: Strategic prioritization of COVID-19 vaccines is urgently needed, especially in light of the limited supply that is expected to last for most, if not the entire, 2021. Dynamically adapting the allocation strategy to the evolving epidemiological situation could thus be critical during this initial phase of vaccine rollout. We developed a data-driven mechanistic model of SARS-CoV-2 transmission to explore optimal vaccine prioritization strategies in China that aim at reducing COVID-19 burden measured through dif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Finally, it would be interesting to analyse adaptive vaccination prioritizations that change as the epidemiological situation evolves over time, but that would require the development of dynamic optimization algorithms that lie beyond the scope of this work 56 . Nonetheless, our study provides estimates of the effect of relaxing NPIs over the course of the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it would be interesting to analyse adaptive vaccination prioritizations that change as the epidemiological situation evolves over time, but that would require the development of dynamic optimization algorithms that lie beyond the scope of this work 56 . Nonetheless, our study provides estimates of the effect of relaxing NPIs over the course of the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from medics, truck drivers were listed as crucial occupations [41]. Yu et al [42] have shown that dynamic vaccination strategies, where it is acceptable to redirect vaccines to regions with the temporarily highest demand, are most effective. Moreover, to provide the most effective protection, the criterion for stratifying the population may change depending on the number of available vaccines, e.g., with low vaccine availability, the prioritization of the population may be related to occupational groups, but with a high number of vaccines, it may be related to age groups [43].…”
Section: Positioning Of the Papermentioning
confidence: 99%
“…The second problem sought to minimize both the number of infected individuals and the quantity of vaccine concentrate administered during treatment. Researchers have also developed a data-driven mechanistic model of COVID-19 transmission to find optimal vaccine distribution strategies, specifically in China, to reduce the effects of the virus [190] .…”
Section: The Four Framework and Literature Reviewmentioning
confidence: 99%